2014
DOI: 10.1210/jc.2013-3842
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Patients With Poorly Differentiated Thyroid Carcinoma

Abstract: With appropriate surgery and adjuvant therapy, excellent locoregional control can be achieved in PDTC. Disease-specific deaths occurred due to distant metastases and rarely due to uncontrolled locoregional recurrence in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
115
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 27 publications
12
115
1
4
Order By: Relevance
“…In contrast, in the present study, locoregional disease was the immediate cause of death in <10% of non-ANA FCDC. Such a difference could be explained in part by the advances in locoregional control in recent years (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in the present study, locoregional disease was the immediate cause of death in <10% of non-ANA FCDC. Such a difference could be explained in part by the advances in locoregional control in recent years (18).…”
Section: Discussionmentioning
confidence: 99%
“…diagnosed solely by MSKCC criteria), these PDTC display additional genetic events (18). When compared with PTC, PDTC are associated with a higher mutation burden and a higher rate (40%) of telomerase reverse transcriptase (TERT) promoter mutations (19).…”
Section: Controversy Surrounding Pdtcmentioning
confidence: 99%
“…This definition differs from the most recent Turin proposal that requires the presence of a solid/trabecular/insular growth pattern in addition to proliferative grading (12). In a recent study, both classifications were found to be comparable in predicting intermediate prognosis of thyroid cancer (13).…”
Section: Histopathologic Analysismentioning
confidence: 80%
“…This thyroid carcinoma subtype has a propensity to metastasize to regional lymph nodes (50%-85%), as well as distantly (36%-85%), most commonly to the lungs and bones (11). Another study reported that distant metastases and local recurrences to be quite variable in patients with PDTC (12).…”
Section: Discussionmentioning
confidence: 99%